Pengaruh Model Joyfull Learning Menggunakan Media Uno Stacko For A Question Terhadap Motivasi Belajar Peserta Didik - mulyadi prasetyo; Nurhidayah; Wiwik Wiji Astuti (Program Studi Pendidikan Biologi, FKIP Unpas, 2024)
The purpose of this study is to ascertain whether the joyful learning model, which makes use of the Uno Stacko For a Question medium, has an impact on the learning motivation of students in class X at SMA Negeri 8 Gowa. At this point, the author uses interviewing techniques to do quantitative research. All two classes of class X IPA at SMAN 8 Gowa served as the study's subjects. Techniques for gathering data included questionnaires and observation. Descriptive statistical analysis was used to examine the data after it was gathered. Ten statements about student motivation were included in the questionnaire used in this study. The data collection instrument for this study was based on the total score obtained by the research students to determine the average score obtained. Determination of the type of answer choices from the questionnaire using a Likert scale through 3 answer categories. The answers to each instrument item using a Likert scale have a very positive to very negative gradation, which can be words such as always, sometimes and never. The results of this study indicate that the application of the joyful learning model using the Uno Stacko For a Question media can increase students' motivation in learning, because the learning is fun and makes students play an active role in the learning process, so it can be concluded that the use of the joyful learning model has an influence on student motivation